High-resolution (19)F MAS NMR spectroscopy: structural disorder and unusual J couplings in a fluorinated hydroxy-silicate. - Griffin, J; Yates, JR; Berry, A; Wimperis, S; Ashbrook, SE (2010)
High-resolution (19)F magic angle spinning (MAS) NMR spectroscopy is used to study disorder and bonding in a crystalline solid. (19)F MAS NMR reveals four distinct F sites in a 50% fluorine-substituted deuterated hydrous magnesium silicate (clinohumite, 4Mg(2)SiO(4)·Mg(OD(1-x)F(x))(2) with x = 0.5), indicating extensive structural disorder. The four (19)F peaks can be assigned using density functional theory (DFT) calculations of NMR parameters for a number of structural models with a range of possible local F environments generated by F(-)/OH(-) substitution. These assignments are supported by two-dimensional (19)F double-quantum MAS NMR experiments that correlate F sites based on either spatial proximity (via dipolar couplings) or through-bond connectivity (via scalar, or J, couplings). The observation of (19)F-(19)F J couplings is unexpected as the fluorines coordinate Mg atoms and the Mg-F interaction is normally considered to be ionic in character (i.e., there is no formal F-Mg-F covalent bonding arrangement). However, DFT calculations predict significant (19)F-(19)F J couplings, and these are in good agreement with the splittings observed in a (19)F J-resolved MAS NMR experiment. The existence of these J couplings is discussed in relation to both the nature of bonding in the solid state and the occurrence of so-called "through-space" (19)F-(19)F J couplings in solution. Finally, we note that we have found similar structural disorder and spin-spin interactions in both synthetic and naturally occurring clinohumite samples.